History and basic principles of transcranial magnetic stimulation - Lopez Chau, Luis (2023)
Transcranial magnetic stimulation (TMS) is a noninvasive technique that uses magnetic fields to stimulate neurons in the cerebral cortex.While electricity has previously been intended to be used in the medical field, the history of TMS dates back to the discovery of electromagnetic induction by Faraday in the 19th century. However, it was not until the 1980s when Anthony Barker developed the first TMS device at the University of Sheffield.TMS works by means of a coil placed against the scalp, thereby producing a magnetic field. This magnetic field can pass through the skull and stimulate cortical neurons. The intensity and frequency of the magnetic field can be adjusted to target specific areas of the brain and produce excitatory and inhibitory effects.The principles of TMS are based on the concept of neuroplasticity, which refers to the brain’s ability to change and adapt in response to new experiences and stimuli. By stimulating neurons in the brain with TMS, it is possible to cause changes in neuronal activity and connectivity, which in turn can lead to cognitive and mood changes.